BOOK REVIEW - S. K. Gupta; M. Sharma (ISBN: 978-81-7233-887-9), Approaches; Trends in Plant Disease Management - (Indian Phytopathology, 2014)
Approaches and Trends in Plant Disease Management - S. K. Gupta and M. Sharma (ISBN: 978-81-7233-887-9), Scientific Publishers (India), 5-A, New Pali Road, P. O. Box 91, Jodhpur 342001; 2014 India; pp429. Price Rs. 2150/- Spectacular progress has been made by India towards ensuring food security buoyed by an unprecedented production of 264 million tons of food grains and 283 million tons of horticultural commodities during 2013-14. This has largely come through area expansion and acceleration of agricultural crop production, besides substantial improvement in productivity. A voluminous gap still seems to exist between per unit area productivity in agriculture in India compared to the western world. Unless sustainability of the growth in food production is insured through continuous improvement in yields from the limited land, it would become extremely difficult for the country to ensure food security for the whopping population of 1.5 billion people by 2030. One of the challenges includes threat due to chronic as well as emerging plant pathogens on the sustainability of agricultural crop production throughout the world. Plant diseases on an average are estimated to cause yield reductions of almost 20 per cent in the principal food and cash crops worldwide. In the past decade, lot of information has been generated by plant pathologists on different aspects of plant diseases and their management options. The book entitled â€œApproaches and Trends in Plant Disease Managementâ€ is an excellent compilation of articles written by knowledgeable and experienced Plant Pathologists of India. In all there are 20 articles each composed in the form of individual chapters dealing with information on the latest developments in the disease management approaches for better, sustainable and environmentally safe disease management strategies. The articles include topics from cultural practices, host-resistance, biological control, integrated disease management, chemical control to molecular markers and biotechnological approaches, each composed pragmatically for sustainable management of plant diseases. The book also contributed few chapters on status and management of some chronic diseases of economic importance to the country. The information has been augmented with coloured photographs, bar diagrams, flow diagrams, tables, microscopic details etc. While I congratulate the contributors for sharing their rich thoughts, they may have improved their articles with some more recent information through literature search. The editors (SK Gupta and Monica Sharma) have done a real good job and possibly could have done better by including some topics on endophytes and nanotechnology in plant disease management. The book provides effective and comprehensive information for researchers, students, teachers and planners regarding present status and possible future strategies in holistic plant disease management. It should find a well-deserved place in the libraries of different institutes and universities engaged in teaching and research in agriculture. Â Pranjib Chakrabarty Assistant Director General (Plant Protection) ICAR, Krishi Bhawan, Dr Rajendra Prasad Road New Delhi 110001